STUDI LITERATUR GAYA MENGAJAR GURU TERHADAP KECERDASAN VISUAL/SPASIAL PESERTA DIDIK SEKOLAH DASAR - Ayu Wida Aulia Sari; Endang M. Kurnianti; Uswatun Hasanah (STKIP Subang, 2024)
The aim of this research is to look at the teaching styles and strategies used by teachers to develop the visual/spatial intelligence of elementary school students. The method used is qualitative research, literature review/literature study method. By reviewing 12 data from the last 5 years consisting of 8 national journal articles, 2 international journal articles, and 2 theses, with similar research categories. The results of the discussion from this research are several efforts needed by teachers to develop the visual/spatial intelligence of their students, including: 1) Teachers recognize the personality of each student, 2) Teachers prepare appropriate teaching strategies, 3) Teachers prepare learning media and tools demonstration, 4) The teacher creates pleasant learning conditions, 5) Collaborates with other fellow teachers, and finally 6) The teacher reflects and evaluates in order to achieve the development of students' visual/spatial abilities/intelligence. Some of these efforts should be carried out with careful planning by the teacher. This is to maximize teacher performance in the learning process in the classroom. Because, if the teacher has maximum performance, then students will also carry out their obligations in learning.